2019
DOI: 10.1007/s10803-019-04037-6
|View full text |Cite
|
Sign up to set email alerts
|

Family Emotional Climate and Children with Autism Spectrum Disorder

Abstract: Little research has examined family emotional climate in the context of having a child with autism spectrum disorder (ASD). The goal of the current study was to determine how the emotional quality of family subsystems (parent-child and parent couple relationships, for both mothers and fathers) combine to create various classes of family emotional climate and to identify predictors of class membership in 148 families of children with ASD. The emotional quality of family subsystems was assessed using Five Minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Exploration of relationships between additional household variables and functional independence was not possible with the current sample due to the lack of variables capturing family structure, and household context. Family and household context such as parent stress, family emotional climate, household chaos, routines, or parent wellbeing has been connected to behavioral outcomes for children with and without ASD (Adams et al, 2019;Greenlee et al, 2018;Hall & Graff, 2012;Hickey et al, 2019;Marsh et al, 2020). Future research should expand on these preliminary findings to further characterize the associations identified and explore how additional factors may be related to measures of income and functional independence outcomes for children with ASD.…”
Section: Discussionmentioning
confidence: 93%
“…Exploration of relationships between additional household variables and functional independence was not possible with the current sample due to the lack of variables capturing family structure, and household context. Family and household context such as parent stress, family emotional climate, household chaos, routines, or parent wellbeing has been connected to behavioral outcomes for children with and without ASD (Adams et al, 2019;Greenlee et al, 2018;Hall & Graff, 2012;Hickey et al, 2019;Marsh et al, 2020). Future research should expand on these preliminary findings to further characterize the associations identified and explore how additional factors may be related to measures of income and functional independence outcomes for children with ASD.…”
Section: Discussionmentioning
confidence: 93%
“…We did not find evidence of between‐parent associations (partner effects). Other studies using APIM analysis in families of autistic children have found partner effects including lower marital satisfaction in mothers being associated with higher stress (GarcĂ­a‐LĂłpez et al, 2016), and lower warmth toward the child by fathers (Hickey et al, 2019). It could be that the global measure of marital satisfaction used in the present study was too broad to pick up on partner effects.…”
Section: Discussionmentioning
confidence: 97%
“…Although research is scant, there is evidence of between‐parent associations between the marital relationship and parenting experiences in the context of autism. Specifically, lower marital satisfaction in mothers was found to be associated with higher parenting stress (GarcĂ­a‐LĂłpez et al, 2016) and lower warmth toward the child (Hickey et al, 2019) in fathers, within families.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the ASD literature, as individual relationships in families of adolescents with ASD were not described as markedly impaired. However, families reported lower functioning of the family and decreased quality of life ( 54 , 55 ). We found in our data that mothers of adolescents with ASD reported less pregnancies and less childbirths ( Table 3A ).…”
Section: Discussionmentioning
confidence: 99%